Desenvolvimento da competência clínica do enfermeiro nos estágios supervisionados : elementos constitutivos e autonomização do sujeito - Polo, Marcela Jossani Ferreira (2019)
This study deals with the clinical competence of nursing students in supervised curricular internships at a federal educational institution. It is assumed that clinical competence constitutes the essence of the nursing profession, and that its development finds in the curricular internships the ideal locus for its reach. The theoretical framework adopted is that of Patrícia Benner, who presents seven domains that are part of clinical competence. The proposed objective is to analyze how the development of clinical competence occurs during supervised curricular internships, in the training of nurses. This is a qualitative, descriptive and exploratory study, developed through document analysis and focus group carried out in 6 meetings - 3 with 11 students from the 8th semester and 3 with 12 students from the 9th semester of the undergraduate nursing course at Universidade Federal de Mato Thick. Minayo's thematic analysis was adopted, and the results submitted to interpretation in the light of the theoretical framework of clinical competence. Two themes resulted from the analysis: "Constitutive elements of clinical competence - convergences and divergences", and "The (co)construction of the nurse's autonomy in supervised curricular internships." The results pointed to the development of clinical competence as multifaceted, procedural, influenced by extrinsic and intrinsic factors to the subject, mediated by the context, organization, legal apparatus, and in particular by the interactions established with teachers, preceptors and other actors present in the clinical scenario. . All these elements contribute to the (co)construction of the future nurse's autonomy. It was concluded, therefore, that the development of clinical competence and the autonomy of nurses in supervised curricular internships is a process of collective construction, both of the subject with himself, his experiences and previous knowledge, but it is strongly influenced by the elements of the environment in which he works. inserts - interactions, work organization, feedbacks and the opportunities to take on a leading role offered to students.